Implication of night-time leisure activities towards place identity of urban public park in Shah Alam and Putrajaya / Mohd Riduan Ngesan - Ngesan, Mohd Riduan (2014)
Urban public parks play a vital role in the social life of the communities. However, hot weather during the days due to the effect of global warming discourages community activities in the urban public parks. Furthermore, the urbanites' daily life is affecting the lack of time and opportunities for leisure and recreational activities. These constraints have changed the behaviour of the urban communities, preferable to carry out their leisure time activities in the urban public parks after the sun has set. It is important to promote leisure in outdoor spaces because most of the community’s activities during night time take place indoor leading to a passive urban lifestyle. Public realm could appear in many ways comprising varied identity, influenced by person or object and context culture or environment. This study investigates a place identity of urban public parks between the city centre of Putrajaya as a new city and the city of Shah Alam as an old city. It is found that people who are living in the case study areas are actively using the urban public parks for leisure and recreational activities during night time. This trend urge by the sufficient lighting, ground material characteristic, design of park facilities and building uses activities in the surrounding of urban public park. These evidences may contribute to a new knowledge of the urban public park design to promote a healthy communities and vibrant urban outdoor spaces during night time.